Corporate wellness programmes and organisational cost savings - Blake, Alison Stephanie (My University, 2016)
There is mounting concern about the increasing cost of healthcare, marketing it unaffordable for more people. Until recently, healthcare has been reactive and curative, in the main" as opposed to proactive and preventive. In the USA and Australia, much research has been undertaken on tne effectiveness of wellness programmes - any programme which aims to educate individuals On unhealthy practices and lifestyles, and thereby pre-empt or avoid severe ill1ness. In this country, wellness programmes are a relatively new approach. [Abbreviated Abstract. Open document to view full version]
This research report submitted to the Faculty of Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management January, 1995
Keywords: Employee health promotion.; Occupational health services.